2018
DOI: 10.1038/s41467-018-05172-x
|View full text |Cite
|
Sign up to set email alerts
|

Propagation topography of redox phase transformations in heterogeneous layered oxide cathode materials

Abstract: Redox phase transformations are relevant to a number of metrics pertaining to the electrochemical performance of batteries. These phase transformations deviate from and are more complicated than the conventional theory of phase nucleation and propagation, owing to simultaneous changes of cationic and anionic valence states as well as the polycrystalline nature of battery materials. Herein, we propose an integrative approach of mapping valence states and constructing chemical topographies to investigate the red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 45 publications
3
63
0
Order By: Relevance
“…1i, k). The difference of the average Ni Kedge absorption energy for the rod-and gravel-NMC is only about 0.12 eV, which is much smaller than the energy resolution of TXM (~0.8 eV) and demonstrates that the two NMCs have similar charge distribution in the pristine state 18,43 .…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…1i, k). The difference of the average Ni Kedge absorption energy for the rod-and gravel-NMC is only about 0.12 eV, which is much smaller than the energy resolution of TXM (~0.8 eV) and demonstrates that the two NMCs have similar charge distribution in the pristine state 18,43 .…”
Section: Resultsmentioning
confidence: 80%
“…Furthermore, these studies have concluded that the improved battery performance was attributed to the enhanced chemomechanical properties. Several studies have attempted to investigate the relationship between the compositional [38][39][40] , morphological 26,41,42 , and charge complexities 15,43 and the battery performance of polycrystalline battery particles. However, there is a lack of a holistic study to spatially and quantitatively elucidate the interplay between grain crystallographic orientation, charge distribution, and battery performance.…”
mentioning
confidence: 99%
“…The latter is well detectable with the help of electrochemical impedance spectroscopy (EIS), as described elsewhere [99]. Mu et al [70,100] proposed that the phase transformation is locally induced by abnormal changes in the valence states of the transition metal ions through modeling and experimental evidences, i.e., reduction of transition metal ions without the intercalation of Li. This could be linked to the interaction between electrolyte and delithiated NMC.…”
Section: Layered-spinel To Rock Salt Phase Transitionmentioning
confidence: 99%
“…In the charged state, the cathode material often exhibits complicated properties that are relevant to the overall battery performance. For example, the formation of morphology defects (Xia et al, 2018), the buildup of charge heterogeneity (Mao et al, 2019) and the reduction in thermal stability (Wei, Zhang et al, 2018;Mu et al, 2018;Xu, Rahman et al, 2018;Yan et al, 2018; are all found in the cathode materials at deeply delithiated states. Therefore, we conducted 3D XANES analysis on a charged LCO particle using the method developed herein.…”
Section: Peak-energy Map Over a Charged Lco Particlementioning
confidence: 99%